2014
DOI: 10.1039/c4ra09862e
|View full text |Cite
|
Sign up to set email alerts
|

FeCo/ZnO composites with enhancing microwave absorbing properties: effect of hydrothermal temperature and time

Abstract: FeCo/ZnO composites were successfully synthesized by a simple one-step hydrothermal process. It is clearly seen that the pencil-like ZnO particles with 3-4 mm in length and 200-300 nm in width are found to grow along the surface of the hexagonal-cone FeCo particles, which form a discontinuous conductive network. Enhanced microwave absorption properties can be obtained for the FeCo/ZnO composites as compared to those of pure FeCo alloy, which is mainly attributed to the better resonance according to an isotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 18 publications
0
34
2
Order By: Relevance
“…Among these hybrids, heteronanostructured hybrids have been proved to exhibit strong EM wave absorption properties because of their interfacial and synergistic effects. Therefore, different categories of heteronanostructured hybrids were developed to further improve their EM wave absorbing capabilities, such as Fe@ZnO11, Fe 3 O 4 @SiO 2 12, Fe 3 O 4 @SnO 2 13, FeCo@ZnO14, Ni@TiO 2 15, and so on16171819. Generally, the previously reported results indicated that the microwave absorption (MA) capability of MAMs was mainly determined by the ε r , μ r , EM impedance matching and microstructure.…”
mentioning
confidence: 99%
“…Among these hybrids, heteronanostructured hybrids have been proved to exhibit strong EM wave absorption properties because of their interfacial and synergistic effects. Therefore, different categories of heteronanostructured hybrids were developed to further improve their EM wave absorbing capabilities, such as Fe@ZnO11, Fe 3 O 4 @SiO 2 12, Fe 3 O 4 @SnO 2 13, FeCo@ZnO14, Ni@TiO 2 15, and so on16171819. Generally, the previously reported results indicated that the microwave absorption (MA) capability of MAMs was mainly determined by the ε r , μ r , EM impedance matching and microstructure.…”
mentioning
confidence: 99%
“…On one hand, the exchange coupling reaction of the magnetic moment between particles can be enhanced with the increase of surface area; on the other hand, the eddy current loss, which may decrease the permeability, is reduced in flaky particles [26]. Additionally, the permeability strongly depends on the saturated magnetization (M s ) of materials ((l 0 À 1)f 0 = M s /3p) [27]. The introduction of nonmagnetic graphene reduces the M s value (shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, the synthesis of magnetic-dielectric composite absorbers, which can take advantages of both a unique permittivity and strong magnetic properties, have received increasing attention [8,9]. Compared with other dielectric additives, carbon-based materials including carbon nanotubes [14], carbon black [15], graphite [16] and graphene [10][11][12][13] possess exceptional advantages of low density, high thermal stability and high chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the FeCo single-phase solid solution obtained in this work. It can be seen that after the reduction reaction, irregular spheres with a diameter of about 150 nm were formed after the precipitation of Fe 2+ , Co 2+ [17,18]. The particles were uniform in size, about 100 nm, and uniform in dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the chemical reduction is the most simple and inexpensive method. For example, Lv et al [17] has obtained nano-FeCo/ZnO composites at 150 °C for 12 hours by traditional one-step method. However, because of less ZnO loaded on the surface of FeCo, this material only exhibited the optimal reflection loss of −31 dB with a 5.5 GHz effective frequency bandwidth.…”
Section: Introductionmentioning
confidence: 99%